Estimation of the Losses of the Ukraine's Financial Potential from Military Conflict - Nataliia Vygovska; Andriy Polchanov (Облік і фінанси, 2019)
Estimation of the loss of financial potential of the state from military conflict is the basis for the development and implementation of state policies to combat the effects of hostilities and strengthen peace. The purpose of the article is to systematize methodological approaches to assessing the financial potential of the state and to substantiate the methods for determining its losses from military conflict for Ukraine in 2014-2017. Theoretical and methodological basis for the formation of the financial potential of the state on the basis of the systematic approach were substantiated. It allowed to clarify the structure of state’s financial potential and to reveal the influence of the interaction of its components and environmental factors on the development of financial potential of the state. It was found that the main methodological approaches to the estimation of the financial potential of the state (additive, multiplicative, secure, based on the analysis of macroeconomic indicators) do not allow to comprehensively assess the level of formation and use of the financial potential, taking into account its structure and resilience to financial threats. On the basis of the additive approach, a quantitative estimation of the volume of financial potential of Ukraine in 2008-2017 was conducted and the stability of the relationship between the financial potentials of authorities, economic entities and households, as well as between the total volume of financial potential of the state and GDP was revealed. It was determined that the financial potential of Ukraine suffered a significant impact of the military conflict, and in order to reach the level of 2013, it should grow annually by an average of 7.45 % during 2018-2022. To reach this level it is necessary to carry out: 1) expanding the powers of local governments in the implementation of local borrowing to stimulate the development of regions; 2) the creation of tax incentives for reinvesting the income of business entities; 3) activation of lending by financial institutions of the private sector through overcoming information asymmetries in the market and ensuring the protection of the rights of borrowers and lenders.